Los límites de la hegemonía estadounidense: deserciones y disidencias en la coalition of the willing (Revista Española de Derecho Internacional, 2006)
The invasion of Iraq by the United States and some allied countries in 2003 shaked the foundations of the international order. The hegemonic power did it at the expense of its own legitimacy and without the support of numerous dissenters. The ad hoc international force known as the «Coalition of the Willing» was intended to avoid or compensate such loss, but it has resulted in an unstable mechanism abandoned by many «Willing» countries between 2003 and 2006. The article analyses the causes and consequences of policies transforming «Willing» allies into «Unwilling» allies of the U.S. Some of them have become «Defectors» whereas others have become «New Dissenters». However, leaving the Coalition of the Willing has borne no significant cost for any of them. The reason lies in the illegitimate nature of the hegemonic power exercised by the U.S. governments and in the non-viability of their imperial project.